An assessment of Trichinella spiralis infection in gonadectomized pigs in Zacatecas, Mexico - Reveles Hernández, Rosa Gabriela (2024)
Objective: To assess the prevalence of Trichinella spiralis in gonadectomized pigs. Material and methods: The study was performed using 9 four-month old pigs, York race, which were divided in three groups: 3 healthy control animals, 3 pigs infected with Trichinella spiralis, and 3 gonadectomized animals that later were infected with T. spiralis. Blood samples were taken from every animal before and after therapy for the detection of anti-T. spiralis antibodies using Western Blot and indirect immunofluorescence techniques. All animals were killed after 6 weeks of being infected with T. spiralis, and tissue samples were obtained for performing assessments using direct methods, such as plate compression and artificial digestion in order to look for the parasite load. Results: Gonadectomized and infected pigs developed an acute presentation of trichinellosis, their parasite load was statistically higher compared to infected non-gonadectomized pigs using ANOVA (P<0.01), and immune methods yielded positive results in both infected groups of animals. Conclusion: The timely diagnosis of Trichinella spiralis in pigs using direct and random assessments by observing the presence of infective worms in brain tissue, together with the detection of anti-T. spiralis antibodies using indirect immunofluorescence and immunoelectrotransference are both efficacious and efficient for the early diagnosis of this infection in animals whose meat is about to be consumed